Phone Snubbing Scale (Phub-S) : A Phubbing Measurement For Young Moslem In Industry 4.0 - Iredho Fani Reza (Islamic Psychology Department, Dakwah Faculty of Universitas Islam Tribakti Lirboyo Kediri, 2021)
The purpose of this study is to develop a measurement scale for phone snubbing among Moslem youth in the era of the industrial revolution 4.0. This research is used a quantitative survey research with the number of respondents N = 503 who were Moslem youths at a university in the Republic of Indonesia which was determined by multistage sampling technique. The instrument used is the Phone Snubbing Scale (Phub-S) which consists of three dimensions - ignore others, dependency on gadgets and social disconnectedness. In analyzing the data through the process of building validity consisting of confirmatory factor analysis and total correlation of corrected items, analyzing internal consistency reliability using Cronbach's alpha technique. The results showed that the Phone Snubbing Scale (Phub-S) has a good item validity and reliability test as a measurement scale for phone insulting behavior young Moslems in the era of the industrial revolution 4.0. The recommended Phub-S items totaling 45 items that have been fulfilled are valid based on testing confirmatory factor analysis (CFA) technique (standardized solution (SS) > 0.4 and T-Values > 1.96), Corrected Item-Total Correlation ≥ 0.30 and with a scale reliability value. 0.932 (Cronbach's Alpha value> 0.8).